2015
DOI: 10.1002/2014ms000371
|View full text |Cite
|
Sign up to set email alerts
|

Isolating effects of terrain and soil moisture heterogeneity on the atmospheric boundary layer: Idealized simulations to diagnose land‐atmosphere feedbacks

Abstract: The effects of terrain, soil moisture heterogeneity, subsurface properties, and water table dynamics on the development and behavior of the atmospheric boundary layer are studied through a set of idealized numerical experiments. The mesoscale atmospheric model Advanced Regional Prediction System (ARPS) is used to isolate the effects of subsurface heterogeneity, terrain, and soil moisture initialization. The simulations are initialized with detailed soil moisture distributions obtained from offline spin-ups usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…The resulting evaporative cooling in convergent zones (e.g., the St. Vrain River in the St. Vrain watershed north of Clear Creek) can even be seen in spatial patterns of surface energy and PBL. These spatial structures—with local increases complementing remote decreases in PBLH—are large‐scale instances of similar patterns shown at the smaller idealized scale (Rihani et al, ). The planetary boundary layer responds to disturbance at the land surface, but the magnitude and direction of its response is contingent upon topography and antecedent moisture conditions.…”
Section: Resultssupporting
confidence: 69%
“…The resulting evaporative cooling in convergent zones (e.g., the St. Vrain River in the St. Vrain watershed north of Clear Creek) can even be seen in spatial patterns of surface energy and PBL. These spatial structures—with local increases complementing remote decreases in PBLH—are large‐scale instances of similar patterns shown at the smaller idealized scale (Rihani et al, ). The planetary boundary layer responds to disturbance at the land surface, but the magnitude and direction of its response is contingent upon topography and antecedent moisture conditions.…”
Section: Resultssupporting
confidence: 69%
“…T sfc indicates the overall energy of the lower atmosphere and is positively associated with GHGs (Raval & Ramanathan, ). SM is directly related to the surface energy budget through both the sensible heat and the latent heat terms, and at low levels, soil moisture generally comes with a high surface sensible heat flux, facilitating the development of the BLH (Mccumber & Pielke, ; Rihani et al, ; Sanchez‐Mejia & Papuga, ). LTS is defined as the difference in potential temperature between 700 hPa and the surface and, therefore, indicates the thermodynamic state of the lower troposphere (Guo, Deng, et al, ; Guo, Su, et al, ), where a larger LTS generally corresponds with a more stable lower troposphere.…”
Section: Resultsmentioning
confidence: 99%
“…Szilagyi et al () further confirmed the link between groundwater and ET in Nebraska through observational data. In turn, these impacts may propagate into the atmospheric boundary layer, affecting the planetary boundary layer height, air temperature, convective available potential energy, and convection precipitation (e.g., Gilbert et al, ; Keune et al, ; Maxwell et al, ; Rahman et al, ; Rihani et al, ). A growing body of literature also suggests that lateral subsurface flow can substantially enhance the T / ET ratio (Fang et al, ; Maxwell & Condon, ), and this effect becomes slightly more significant for higher model resolutions (Shrestha et al, ).…”
Section: Introductionmentioning
confidence: 99%